Introducing Literary Studies - Middeke, Martin; Müller, Timo; Wald, Christina; Zapf, Hubert (My University, 2012)
Literary studies is a discipline with a long history, during which it has been influenced by fields that we would no longer regard today as central to literary studies, chiefly by biblical exegesis. Hence, the question arises as to what we consider as literature—we instantly would include written imaginative texts such as novels, poems and plays, but what about song lyrics, rap or performance poetry? In the context of increasing interest in psychological and sociological texts, the term could also be extended to, for instance, essays, political speeches, magazines, or newspapers. Scholars have proposed competing notions of literature, and today we can differentiate between a narrower and a broader understanding of (literary) texts (the latter would include rap lyrics for instance). The chief quality that helps us distinguish literature from other text sorts is the question of its pragmatic use.
Keywords: 800